EXERCISE AND PEAK BONE MASS: RECOMMENDATION FOR BUILDING HEALTHY BONES IN CHILDREN - A Andi Kurniawan (Faculty of Medicine Universitas Kristen Duta Wacana, 2016)
Regular Physical activity (PA) and exercise plays a vital role in the health and well-being of people of all ages, and its associated with positive outcomes relating to weight status, cardiometabolic markers, chronic disease prevention, bone health and mental health. Genetic factors are the strongest determinants of bone mass, but PA and exercise with loading of the bone also has a major impact on bone mass as well as on bone strength. Physical activity has been proposed as a key factor for developing healthy bones in childhood and adolescence, mainly when high-impact and weight-bearing exercise above a certain intensity and duration. It has been associated with bone accretion showing an important osteogenic effect, mainly when high-impact and weight bearing physical activity occur. Muscle mass is also a determinant of bone development. Several studies have examined the association between PA and bone health among youths.